Surface characteristics and biocompatibility of cranioplasty titanium implants following different surface treatments. Issue 4 (April 2018) - Hatamleh, Muhanad M.; Wu, Xiaohong; Alnazzawi, Ahmad; Watson, Jason; Watts, David
Abstract: Objective: Surface and mechanical properties of titanium alloys are integral for their use in restoring bone defects of skull and face regions. These properties are affected by the method of constructing and surface treatment of the titanium implant. This study aimed to investigate the effects of titanium finishing protocols on the surface morphology, hardness and biocompatibility of TiAl6V4. Methods: Square shaped TiAl6V4 specimens (ASTMF68 ) (10 × 10 × 0.5 mm) were divided into seven groups of different surface treatments (n = 10). The treatments included mechanical polishing, sandblasting with AL2 O3 (50 μm), immersion in different acids, and/or electro-chemical anodization. Weight loss %; 3D micro-roughness; Knoop micro-hardness, and osteoblast cell attachment and proliferation (after 3 days) were determined for each specimen. Data was analysed using one way ANOVA and Dunett T3 post-hoc tests, and t -test (p < 0.05). Results: Weight loss % was in the range of 1.70–5.60 as mechanical polishing produced the highest weight loss, followed by sandblasting, and combined protocol of mechanical polishing and acid treatment (p < 0.05). Micro-roughness values (μm) were in the range of 2.81–16.68. It was the highest for control specimens (p < 0.05), and smoothest surfaces after combined mechanical polishing and acid treatment; or after electro-chemical treatment (p < 0.05). Micro-hardness values (MPa) ranged 170.90–442.15 as sandblasting with/without acid treatment caused statically significantly the highest values (p < 0.05) while control and mechanically polished specimens had the lowest values (p < 0.05). All treatments produced equally biocompatible surfaces (p > 0.05) after 1 h or 3 days. Furthermore, osteoblast cell proliferation statistically significantly increased after 3 days among each surface treatment (p < 0.05). Significance: Different finishing treatments have variable effect on cranioplasty titanium surface loss, micro-roughness and micro-hardness but constant improved biocompatibility effect. Electro-chemical treatment caused less material loss and produced biocompatible smoothest surface of comparable hardness; hence it can be suitable for cranioplasty titanium surface finishing.